Relationship of exposure to public affairs news with cognitive, attitudinal and behavioural dimensions of ethnic tolerance among Malaysian youths - Tamam, Ezhar; Yee, Wendy Mei Tien; Idris, Fazilah; Hamzah, Azimi (Penerbit Universiti Sains Malaysia, 2006)
This study examined the relationship and contribution of exposure to public affairs news vis-à-vis the cognitive, and attitudinal components and the behavioural component of ethnic tolerance among Malaysian youths aged between 15 to 25 years. The survey data were collected using self-administered questionnaires. A total of 2,906 youths voluntarily participated in a survey. The results of regression analyses showed that when exposed to public affairs news, the cognitive and attitudinal components of ethnic tolerance were significant predictors and accounted for 16.5% of the variance in the behavioural component of ethnic tolerance. The cognitive component of ethnic tolerance was a better predictor, followed by the attitudinal component and exposure to public affairs news.